Agrochemicals Desk Reference, 2nd Edition - Montgomery, John H. (CRC Press, 2009)
The Second Edition of the Agrochemicals Desk Reference is a revised, up-to-date volume inspired by the growing number of research publications and continued interest in the fate, transport, and remediation of hazardous substances.